Integration of the Buddhist Principle in Educational Administration - (จงสกุลศิริ), พระมหาเผด็จ จิรกุโล; ทัศนศรี, ศิริพร (Journal of Educational Review Faculty of Education in MCU, 2018)
Buddhism is the science of learning with the cessation of suffering as its ultimate goal. The Buddha’s teachings are for calmness, nonviolence and happiness and peacefulness of the practitioners and the people concerned. The learners of Buddhism can evaluate their own learning by themselves as the Buddha said, ‘A wise man can realize by himself.’ There are teachings concerning learning and education in Buddhism. If those teachings are to be studied, interpreted, explained, classified and integrated with modern system, that can be a successful and effective tool in education administration and human development. Integrating Buddhist principles to educational administration is to put into practice appropriately in improving the quality of human life, developing environmental quality and bringing society to a happy society.